Green synthesis of silver nanoparticles using aqueous leaf extract of Premna integrifolia (L.) rich in polyphenols and evaluation of their antioxidant, antibacterial and cytotoxic activity. Issue 1 (1st January 2019) - Singh, Chandrashekhar; Kumar, Jitendra; Kumar, Pradeep; Chauhan, Brijesh Singh; Tiwari, Kavindra Nath; Mishra, Sunil Kumar; Srikrishna, S.; Saini, Rajesh; Nath, Gopal; Singh, Jasmeet
Abstract: Premna integrifolia L. is widely distributed in tropical and subtropical regions. In the present study, green silver nanoparticles were synthesized efficiently after mixing 1 mmol/L AgNO3 and 4% aqueous leaf extract at neutral pH (7.0) after 25 min sunlight exposure. The aqueous leaf extract was enriched with polyphenols. It had higher flavonoid (67.23 ± 1.23 µg/mg gallic acid equivalent) than phenolic content (58.10 ± 2.29 µg/mg rutin equivalent). The bio-synthesized silver nanoparticles were characterized by different spectroscopic and microscopic studies. The synthesized nanoparticles were spherical in shape and ranged from 9 to 35 nm in size. The crystalline nature of the nanoparticles was confirmed on the basis of high-resolution transmission electron microscopy (HRTEM), high-resolution scanning electron microscopy (HRSEM), X-ray diffractometry (XRD) and selected area electron diffraction (SAED) analyses. The presence of silver ions in the biosynthesized nanoparticles was demonstrated based on energy-dispersive X-ray (EDX) data (3.5 keV). The functional groups involved in the nanoparticle synthesis were analysed using FT-IR. These silver nanoparticles showed good antibacterial activity against human pathogenic gram-positive ( Staphylococcus aureus, Enterococcus faecalis ) and gram-negative ( Shigella dysenteriae, Shigella flexneri and Vibrio parahaemolyticus ) bacteria. The silver nanoparticles exhibited good in vitro antioxidant and cytotoxic activity to human cervical cancer cell line (SiHa).